Perlindungan Hukum Terhadap Anak Temuan - Khairilina (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2021)
In the current era of globalization, many human behaviors, especially teenagers, are leaving the corridors and regulations, both religious and state regulations. This can be seen from the large number of children born out of wedlock which are then discarded by the mother who gave birth to them to cover their disgrace or do not want to be responsible for their actions. However, apart from these immoral incidents, there are also other unwanted events which are the destiny of Allah as a calamity or disaster such as earthquakes and tsunamis. Of these two incidents, there were many sad events, including children who were abandoned, losing their parents and later being found by other people. In this regard, the content that will be discussed in this paper is about Legal Protection of Finding Children. What is the authority and involvement of the State, especially in Indonesia in terms of protection for these unfortunate children and what is the Islamic view of finding children. Whether it is related to the civil rights of children, the findings and procedures for obtaining their rights.